Satellite Tracking of Eastern Chukchi Sea Beluga Whales into the Arctic Ocean - Suydam, Robert S.; Lowry, Lloyd F.; Frost, Kathy J.; O'Corry-Crowe, Greg M.; Pikok, Jr., Danny (ARCTIC, 2001)
Beluga whales (Delphinapterus leucas) congregate in nearshore waters of the eastern Chukchi Sea, especially in Kotzebue Sound and Kasegaluk Lagoon, in June and July. Where they travel after they leave this area was unknown before this study. We live-captured five belugas in Kasegaluk Lagoon and attached satellite-linked depth recorders to them. The belugas, caught between 26 June and 1 July 1998, were all males, ranging in length from 398 to 440 cm. A 310 cm gray beluga accompanied the smallest male. Two tags transmitted for only about two weeks, during which time one animal remained in the vicinity of Icy Cape, 80 km north of the capture site, and the other traveled to Point Barrow, about 300 km north. The other three tags operated for 60-104 days, and those belugas traveled more than 2000 km, reaching 80° N and 133° W, almost 1100 km north of the Alaska coast. This journey required them to move through 700 km of more than 90% ice cover. Two of the whales then moved southward into the Beaufort Sea north and east of Point Barrow. Two whales later moved to an area north of the Mackenzie River delta, where they spent 2-3 weeks before once again heading southwest towards Barrow. En juin et juillet, des bélougas (Delphinapterus leucas) se rassemblent dans les eaux littorales de l'est de la mer des Tchouktches, en particulier dans le détroit de Kotzebue et la lagune de Kasegaluk. Avant la présente étude, on ne savait pas où ils allaient après avoir quitté la région. Dans la lagune de Kasegaluk, on a capturé vivants cinq bélougas qu'on a équipés de sondeurs acoustiques en liaison avec un satellite. Les bélougas, capturés entre le 26 juin et le 1er juillet 1998, étaient tous de mâles, et mesuraient de 398 à 440 cm de long. Un bélouga gris de 310 cm accompagnait le plus petit mâle. Deux sondes n'ont retransmis que durant deux semaines, au cours desquelles un individu est resté aux environs du cap Icy, à 80 km au nord du site de capture, tandis que l'autre s'est rendu à la pointe Barrow, à environ 300 km au nord. Les ...